Nauczanie ku transgresji. Podmiotowe doświadczenie edukacyjne w modelu pedagogiki zaangażowanej bell hooks (Glorii Jean Watkins) - Drozdowicz, Jarema (Kultura-Społeczeństwo-Edukacja, 2020)
The African-American scholar bell hooks is a well known figure in the Western academic milieu. This article makes an attempt at presenting the model of engaged pedagogy represented in hook’s works and her public appearances. This is done by highlighting the issue of subjective experience in the educational setting. Hook’s concept of race and gender is brought to attention to present the aforementioned issue within the broader context of her socio-cultural concepts she is known for. The outcome of this reconstruction shows us that the model of engaged pedagogy is developed by hooks into a wide set of postulates of structural change of the American schooling system, as well systems in other parts of the world. Therefore, it seems plausible to put her works within the tradition of critical pedagogy as found in the works of Paulo Freire and others.